The police leaflet of the Kerch-Yenikalsky city government as a source of criminal journalism in the pre-revolutionary period of the late XIX – early XX centuries - Arzy Khas’yanova (Крымское историческое обозрение)
One of the factors in the process of modernization of the Russian Empire was the development of periodicals. The “Great Reforms” of the 1860-1870s, the relaxation of censorship rules in relation to the time press, led to an increase in the number of publications and their circulation. This article describes a detailed evolution of the periodical press in the Taurus province of the late XIX – early XX centuries. At this time there was a separation of genre types of journalism, criminal in particular. The ancestor of this trend in the Crimea was the publication of the “Police Leaflet of the Kerch-Yenikalsky Town Administration”. This article presents the stages of the origin, formation and activities of the newspaper.